Erectile Dysfunction Preceding Clinically Diagnosed α-Synucleinopathies: A Case-Control Study in Olmsted County - Shemonti Hasan; Michelle M. Mielke; J. Eric Ahlskog; James Bower; Pierpaolo Turcano; Rodolfo Savica (Parkinson's Disease)
Objective. Autonomic symptoms are common in α-synuclein disorders: multiple system atrophy (MSA), Parkinson’s disease (PD), dementia with Lewy bodies (DLB), and Parkinson’s disease with dementia (PDD). These symptoms may precede the motor findings/clinical diagnosis by years. Erectile dysfunction (ED) is an autonomic symptom that has rarely been studied in these α-synuclein disorders. In this population-based, case-control study, we investigated the association between premonitory erectile dysfunction surfacing prior to the clinical-motor manifestations of these α-synucleinopathies. Methods. We used the medical record-linkage system of the Rochester Epidemiology Project to identify cases of α-synucleinopathies in Olmsted County from 1991 to 2010. Each male case was matched by age (±1 year) of symptom onset and sex to a control. We reviewed complete medical records of cases and controls to detect erectile dysfunction prior to the clinical-motor onset of α-synucleinopathies of any type. We used conditional logistic regression to calculate the odds ratio of all α-synucleinopathies, as well as by type, adjusting for diabetes, coffee, and smoking. Results. A history of male erectile dysfunction was associated with 1.5-fold increased odds of an α-synucleinopathy diagnosis of any type in univariate analyses (p=0.06). When stratifying α-synucleinopathies by type, early erectile dysfunction was most frequent in MSA cases than matched controls (45% vs. 9%). Premotor phase ED was next most frequent among the DLB cases (46% vs. 27% among the controls; OR = 2.83, p=0.03; when adjusted for diabetes, smoking, and coffee, OR = 2.98, p=0.04). Premotor phase ED was not significantly associated with PD or PDD. Conclusions. Early erectile dysfunction may be a premotor symptom of MSA and DLB, reflecting premonitory dysautonomia. It was not associated with premotor PD or PDD.